Trichotomy of awareness, outlook and practice of food handlers towards food and water safety in food establishments in Addis Ababa, Ethiopia - Aderajew Mekonnen Girmay; Sirak Robele Gari; Azage Gebreyohannes Gebremariam; Bezatu Mengistie Alemu; Martin R. Evans (AIMS Press, 2020)
Introduction: Food and waterborne diseases are the commonest global public health problems. Specifically, in Ethiopia, public health problems associated with deterioration of food and water safety situations are much more complicated due to poverty, economic and environment related risks. Awareness, outlook and practice of food handlers are the three important factors that play major roles in the occurrence and outbreak of food borne diseases. Therefore, this study aimed to evaluate awareness, outlook and practice of food handlers towards food and water safety. Methods: Institution based cross sectional study was conducted among food handlers of Addis Ababa city administration. In this study, 416 participants were selected using a stratified, simple random sampling technique; and were interviewed using structured questionnaire. Linear Regression Model and analysis of variance were used for data analysis. Results: In this study, 55.5%, 66.1% and 60.6% of the food handlers had good awareness, outlook and proper hygiene practices respectively. This study revealed that, 17.5% and 23.1% of the respondents did not know about food and water borne disease respectively. Only 39.4% of the participants had proper practice of covering mouth with tidy cloth when they cough. Moreover, 75.7% of the food handlers reported that they did not wear personal protective devices during the working time. Predictor variables like educational status and length of work experience were correlated positively and significantly with awareness. However, being married was correlated negatively with awareness. Conclusion: Assessing awareness, outlook and practice of food handlers regarding food and water safety is a vital activity to reduce public health problems. Significant number of food handlers had poor awareness, outlook and practice towards food and water safety. There is a call for enhancing the awareness, outlook and practice of food and water safety to achieve an excellent practice. Better food and water safety policy and firm regulatory actions are needed.